"Any Alternative Is Great If I'm Incarcerated": A Case Study of Court-Ordered Community Service in Los Angeles County. (January 2021) - Sonsteng-Person, Melanie; Herrera, Lucero; koonse, Tia; Zatz, Noah D.
California courts increasingly order community service for those convicted of nonviolent and minor misdemeanors or infractions, assigning unpaid work to be performed. While court-ordered community service has been used as an alternative to incarceration and the payment of fines, little is known about the monetary and personal costs for those completing it. A case study design is used to examine court-ordered community service performed in Southeast Los Angeles. Data were gathered from a quantitative dataset of 541 court files of those assigned to community service and 32 in-depth interviews with attorneys and court-ordered community service workers. While the quantitative data and Attorney interviews found that negative outcomes of community service can drive community service workers deeper into debt and result in new warrants that place defendants at risk for rearrest, individuals that completed community service appreciated the opportunity to pay off their criminal justice debts and stay out of jail.